Collaboration, Invisible Work, and the Costs of Macrotask Freelancing - Hulikal Muralidhar, Srihari; Rintel, Sean; Suri, Siddharth (CSCW 2022, 2022)
Online labour platforms promise efficient, low-friction matching of workers with clients at scale and on-demand. Prior studies on Upwork have shown that the combination of specialized knowledge and expertise, high autonomy, and extent of client-worker engagement makes macrotasks a unique category of ‘on-demand’ work. However, there is a need to unpack the nature of macrotask work from the freelancers’ perspective. Based on a qualitative study of 21 freelancers on Upwork, this paper fills this important gap by delineating how freelancers reason about accomplishing macrotasks, their interaction with clients, the key challenges that they face in various stages of the work process, and the strategies they devise to mitigate the costs and overhead. This paper shows that freelancers perceive accomplishing macrotasks as a collaborative achievement with the client. It also demonstrates that the skill-intensive nature of tasks implies that matching freelancer with the task/client is of enormous importance. It describes three programmatic solutions that the platform offers to facilitate the matching process along with their benefits and limitations. It, then, shows how freelancers seek to minimize the costs and work associated with matching and collaboration through repeat hiring along the benefits they result in. Lastly, the paper highlights how the same set of core issues is mirrored for both the freelancer and client sides of the market, which need to be addressed in order to enhance the ease and effectiveness of client-freelancer collaboration.